Nanoparticles Functionalized with Collagenase Exhibit Improved Tumor Accumulation in a Murine Xenograft Model. (10th November 2014) - Murty, Surya; Gilliland, Taylor; Qiao, Peter; Tabtieng, Tate; Higbee, Elizabeth; Zaki, Ajlan Al; Puré, Ellen; Tsourkas, Andrew
<x xml:space="preserve">Abstract</x> Nanoparticles have garnered widespread interest for both the imaging and treatment of cancer due to their unique and tunable pharmacokinetics and their ability to carry a high payload of diverse compounds. However, despite these favorable attributes, the extent of tumor accumulation can be severely restricted due to the dense stroma surrounding the often‐permeable blood vessel wall and high intratumoral pressure. In this study, it is investigated whether modifying the surface of pegylated gold nanoparticles (AuNPs) with collagenase could improve the accumulation of nanoparticles within a murine tumor xenograft. It is determined that collagenase remains active after surface conjugation and the presence of collagenase has no measureable effect on cell proliferation in vitro. Following intravenous injection, the largest fractions of collagenase‐labeled AuNPs are found in the liver and spleen. Histological analysis reveals no signs of toxicity in either of these organs. Blood chemistry reveals normal levels of liver enzymes, but a slightly elevated level of total bilirubin. Within the tumor, AuNPs labeled with collagenase exhibit a 35% increase in accumulation compared with unlabeled AuNPs. Therefore, these studies provide preliminary evidence that the functionalization of nanoparticles with collagenase represents an effective and safe approach to improve tumor accumulation.